Characterisation of a novel stimuli-responsive polymers for protein refolding - Ang, Jing Mei (2009)
During bioprocessing, there are many points at which protein can aggregate, reducing the overall protein refolding yield. A novel stimuli responsive polymer: Poly (L-lysine iso-phthalamide) was investigated in this study to examine its potential use as an additive to improve refolding yield of hen egg white lysozyme (HEWL).